Broadband and Energy‐Concentrated Absorber Based on Hemispherical‐Embedded Structure. Issue 3 (20th January 2023) - Wu, Zhe; Liang, Zhongzhu; Shi, Xiaoyan; Yang, Fuming; Dai, Rui; Hou, Enzhu; Sun, Wenwen; Qin, Zheng; Xin, Wei; Xu, Haiyang
Abstract : Spatially concentrated absorption is able to form local hotspots and helps to generate hot electrons with higher energy than free electrons, which can be used to improve the performance of hot electron devices. Herein, a broadband, wide‐angle, and highly concentrated metamaterial absorber operating in near‐infrared and midinfrared bands is proposed. The absorptivity of the proposed absorber exceeds 90% in the wavelength range of 2.0–5.4 μm, and the average absorptivity at 2.0–5.4 μm reaches 93.5%. Moreover, the absorber can highly concentrate the energy of the incident light on a point on the bottom surface of the device; the area with concentrated energy only accounts for 1.4% of the total area of the bottom, thus forming a hotspot. Meanwhile, the absorber can still maintain an average absorptivity of more than 85% when the incident light angle of various polarization directions reaches 60°. These characteristics enable the device to provide a solution to improve the performance of hot electrons, energy collection, and imaging devices. Abstract : A broadband, wide‐angle, and energy‐concentrated absorber based on a hemispherical‐embedded structure is studied. The energy of the incident light highly concentrates on a point on the bottom surface of the device, which is able to provide a solution to improve the performance of hot electrons, energy collection, and imaging devices.